Tissue development and carcass characteristics of pure male and female originally from Nellore breed at yearling in the north region from Mato Grosso - Bem, J. C. T. D.; Rosa, A. C.; Moreira, P. S. A. (Scientific Electronic Archives, 2016)
The aim of this study was to estimate tissue development and carcasscharacteristics of pure males and females of Nellore breed at yearling using an ultrasound. The data are from Farm BAMA, located in the city of Juara, Northof Mato Grosso. The males’ data were collected for three consecutive years (2012-2014) andthe ones from females were collected during two consecutive years (2013 and 2014) byPecus Company - US Livestock Advisory LTDA production. The experimental groups were split according to sex (male or female) and year of birth; being the male’s groups: T1: 83 malesborned in 2011, T2: 97 males borned in 2012 and T3: 247 males borned in 2013; and female’s groups: T1: 326 females borned in 2012 and T2: 82 females borned in 2013. The characteristics analyzed were: weight, ribeye area, ribeye area for 100 kg, subcutaneous adipose tissue thickness, subcutaneous adipose tissue thickness for 100 kg, marbling and fat thickness on the back. The software used for the interpretation of the images was the BIA - Designer Genes. The values found for the characteristics analyzed in this study were in general higher than the average for Nellore breeds. The aim of this study was to estimate tissue development and carcasscharacteristics of pure males and females of Nellore breed at yearling using an ultrasound. The data are from Farm BAMA, located in the city of Juara, Northof Mato Grosso. The males’ data were collected for three consecutive years (2012-2014) andthe ones from females were collected during two consecutive years (2013 and 2014) byPecus Company - US Livestock Advisory LTDA production. The experimental groups were split according to sex (male or female) and year of birth; being the male’s groups: T1: 83 malesborned in 2011, T2: 97 males borned in 2012 and T3: 247 males borned in 2013; and female’s groups: T1: 326 females borned in 2012 and T2: 82 females borned in 2013. The characteristics analyzed were: weight, ribeye area, ribeye area for 100 kg, subcutaneous adipose tissue thickness, subcutaneous adipose tissue thickness for 100 kg, marbling and fat thickness on the back. The software used for the interpretation of the images was the BIA - Designer Genes. The values found for the characteristics analyzed in this study were in general higher than the average for Nellore breeds.